Newman's Error Analysis (NEA) in Solving Computational Thinking Problems on Indefinite Integral Material - Lisa, Lisa; Simamora, Elmanani; Mulyono, Mulyono; Napitupulu, E. Elvis; Panjaitan, Asmin (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
The initial abilities of students in the Integral Calculus course reveal that many have not yet grasped the fundamental concepts of integration. Out of 20 students given integral problems, only 6 students (30%) were able to answer correctly, while 14 students (70%) made errors. These errors in the Calculus course need to be analyzed further to assist lecturers and students in identifying weaknesses in the learning process and address or at least reduce similar mistakes in the future. This study employs a descriptive qualitative approach, with 20 second-semester students from the Mathematics Education program at IAIN Lhokseumawe as the research subjects. The findings indicate that students with very high and high computational thinking skills did not make errors compared to those with moderate, low, and low computational thinking skills. Students with moderate computational thinking skills tended to make errors in processing and answer writing. In contrast, students with low and very low computational thinking skills more frequently encountered transformation, processing, and answer-writing errors. Transformation errors occur when students make mistakes in calculations or during the process skill stage. These errors are often caused by students’ difficulty structuring solution steps, leading to misunderstanding the problems. Most students were also unable to reformulate the problems into forms suitable for the appropriate solution method, resulting in their inability to proceed with the calculations. Based on the error analysis using Newman’s Error Analysis (NEA) method, the most common types identified were transformation, processing, and answer-writing errors.